Khāḍilakarāñcā Rudra - Khāḍilakara, Krshṇājī Prabhākara, 1872-1948 (SAMP early 20th-century Indian books project ;, 1945)
Interpretation of Vedas. Yajurveda. Krshṇayajurveda (Taittirīyasaṃhitā). Rudrādhyāya.